Os fatores de proteção e risco para cursar uma graduação em alunos prounistas - Karnal, César Leonardo (Universidade do Vale do Rio dos Sinos, 2015)
This research aims at analyzing protection factors and risk factors for PROUNI students to study an undergraduation course in a university in the South of Brazil. Being approved at ENEM, and consequently, receiving PROUNI grant are not enough to keep learners studying and finishing their courses. Students have to manage their studies, their work and family life along the university course. In this research, resilience was used as an attempt to understand the student´s capacity to feel stronger after a crisis situation. The methodology used was qualitative and exploratory. We used a focal group and a sociodemographic questionnaire as data collection instruments. Moreover,thirteen students participated. Data were explored using content analyses from Bardin. Results show thatfamily can be a risk factor as well as a protection factor when studying an undergraduation course, it is either a risk or a protection depending on the support and incentive offered. In addition to that, other ways to offer social support are described as meaningful (pairs, professors, managers). Participants revealed that, although they are concerned with their difficulties, overloaded and stressed out, planning and putting on effort and determination to finish their courses is still worthwhile. It can make a difference in financial and social terms and also offer perspective to their future lives.
Keywords: Prounistas; Fatores de proteção; Fatores de risco; Resiliência; Graduação; PROUNI students; Protection factors; Risk factors; Resilience; Undergraduation; ACCNPQ::Ciências Humanas::Psicologia